AB initio study of structural stability and electronic properties of ZrO2-xSx for 0<x<2 - Mulaudzi, Masilu Godfrey (My University, 2015)
While the effect of sulphur on c-ZrO2 is often considered in application of advanced solid oxide fuel cells and biomass gasification cleanup, there has been little study on the effect of sulphur on general structure of c-ZrO2. In this work a study of the structural, energetic, electronic and elastic properties of doped c-ZrO2-xSx, t-ZrO2xSx and m-ZrO2-xSx solid solutions has been carried out using ab-initio total energy calculation of the density functional theory under plane wave pseudopotential method within generalized gradient approximation using the self-consistent virtual crystal approximation (VCA). It has been shown that all the calculated properties obtained after relaxation are in good agreement with available experimental and other calculated values, particularly at x=0. Furthermore, the formation and cohesive energies were calculated to determine the relative stability of all three non-sulphated and sulphated polymorphs of ZrO2. The density of states and band structures have been computed for x = 0.0 - 0.5, and the actual size of the band gap of ZrO2 compounds narrowed with partial replacement of oxygen by sulphur, while peaks above Fermi level move towards the Fermi level. The material changes its insulating properties to semiconductor material as a function of sulphur concentration, which might be useful for potential application. We also investigated and calculated, for the first time, the effect composition variation on mechanical stability, the independent elastic constants and other elastic parameters of the sulphated compounds. The polycrystalline bulk moduli, shear moduli, Young and Poisson’s ratio have been deduced by using Voight-Reuss-Hill (VRH) approximation. In addition we also show the geometric and electronic structure of pure ZrOS and ZrS2 and compare them with the obtained geometric and electronic structures of ZrO2-xSx.
Thesis (M.Sc. (Physics)) -- University of Limpopo, 2015
Keywords: Zirconium oxide; Zirconium oxide.; Structural stability.